BIOACTIVITY CHARACTERIZATION OF PURIFIED RECOMBINANT HYPOTHETICAL PROTEIN CODED BY OPEN READING FRAME-112 OF STREPTOMYCES. - Al-Obaidi, R. M.; Salih, G. F.; Nore, B. F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was aimed to investigate the Open Reading Frame-112 (ORF-112) gene, which encoded for a hypothetical 218 amino acids protein in Streptomyces bacteria. A complete ORF-112 gene was synthesized, with addition of a 6xHis-Tag at the N-terminal location. The synthesized DNA nucleotides were sub-cloned into bacterial expression plasmid pBAT4. The pBAT4-ORF-112 plasmid transformed in bacterial cells BL21(De3)pLysS, intended for protein over expression, induced by isopropyl β- d-1-thiogalactopyranoside (IPTG). The IMAC affinity chromatography technique was deployed for protein purifications. Highly-purified fractions of ORF-112 were achieved by using affinity Ni++-columns. The purified ORF-112 protein was tested for possible biological activity. The SDS-PAGE analysis exhibited a soluble 30 kDa size purified ORF-112 protein which showed a slight gel shifting from the predicted size. The virulent activity test on purified fractions of ORF-112 was measured using the Disk Diffusion Test and it disclosed a clear zone formed in response to fungi Candida albicans growth. The data implies that the ORF-112 protein has an acceptable protective effect against the fungus C. albicans as compared to positive control ketoconazole (KCZ) (P < 0.05) while the protein has a significantly lower protective effect against the fungus than Itraconazole (ICZ) (P > 0.05). The results clarify the hypothetical ORF-112 protein is a novel protein with protective response effect against fungi cells C. albicans on disk-diffusion.test.